Gender - Tripp, Anna (Palgrave, 2000)
Critical debates about gender are intense, diverse, and vigorously ongoing, now bearing on every aspect of cultural endeavour and enquiry. What becomes clear when investigating this subject is that, while feminism has obviously played a pioneering role in the articulation, politicization, and development of questions of gender, the field of enquiry into gender is broader than feminism. This reader takes into account these considerations and offers an accessible and stimulating introduction to the sheer breadth and diversity of work on gender. While feminism is represented in its vitality and variety, so too is work on masculinities, psychoanalytical accounts of gender, and more recent developments such as queer theory.